Clinical, hematological, and molecular characterization of sickle cell anemia pediatric patients from two different cities in Brazil Caracterização clínica, hematológica e molecular de crianças portadoras da anemia falciforme em duas diferentes cidades do Brasil - Isa Menezes Lyra; Marilda Souza Gonçalves; Joseffina A. Pellegrinei Braga; Maria de Fátima Gesteira; Maria Helena Carvalho; Sara Terezinha Olalla Saad; Maria Stella Figueiredo; Fernando Ferreira Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
This study focused on clinical, hematological, and molecular aspects of sickle cell anemia pediatric patients from two different cites in Brazil. Seventy-one patients from São Paulo and Salvador, aged 3 to 18 years, were evaluated. Hematological analyses, betaS globin gene haplotypes, and alpha2 3.7kb-thalassemia were performed. Numbers of hospitalizations due to vaso-occlusive crises, infections, stroke, and cholelithiasis were investigated. São Paulo had more hospitalizations from vaso-occlusion, cholelithiasis, and stroke than Salvador. The Ben/CAR genotype predominated in both cities. alpha2 3.7kb-thalassemia had a frequency of 28.2% in Salvador, mostly with Ben/CAR genotype (45.0%), while São Paulo had 22.5% with similar frequencies of the Ben/ CAR and CAR/CAR genotypes. Sickle cell anemia patients from São Paulo also had more episodes of stroke, which was observed among CAR/CAR, atypical, and BEN/CAR haplotypes. In Salvador stroke was only observed in the Ben/CAR genotype. Cholelithiasis had similar frequencies in the two cities. These data suggest a milder phenotype among patients in Salvador, possibly due to genetic, environmental, and socioeconomic factors. Further studies are needed to elucidate modulating factors and phenotype association. O objetivo desse estudo foi avaliar aspectos clínicos, hematológicos e moleculares de pacientes pediátricos portadores de anemia falciforme em duas cidades brasileiras: Salvador e São Paulo. Foram estudados 71 pacientes com idades variando entre 3 a 18 anos, analisando-se os seguintes aspectos: perfis hematológicos, haplótipos dos genes da globina beta, presença de talassemia alfa-2(3.7kb), número de internações por vaso-oclusão, infecção, presença de acidente vascular cerebral e litíase biliar. O genótipo Ben/CAR predominou nas duas cidades. Talassemia alfa-2(3.7kb) teve freqüência de 28,2% em Salvador e 22,5% em São Paulo. Os pacientes de São Paulo apresentaram um número maior de internações por vaso-oclusão nos diferentes genótipos. Esses dados sugeriram um fenótipo com menor gravidade clínica nos pacientes de Salvador, possivelmente relacionados a fatores genéticos, ambientais e sócio-econômicos. Estudos adicionais necessitam ser realizados com intuito de elucidar os efeitos moduladores na expressão gênica da doença.